Variations in Low-Risk Cesarean Delivery Rates in the United States Using the Society for Maternal-Fetal Medicine Definition. Issue 2 (February 2022) - Ouyang, Lijing; Cox, Shanna; Ferre, Cynthia; Xu, Likang; Sappenfield, William M.; Barfield, Wanda
Abstract : OBJECTIVE: To assess variations in low-risk cesarean delivery rates in the United States using the Society for Maternal-Fetal Medicine (SMFM) definition of low-risk for cesarean delivery and to identify factors associated with low-risk cesarean deliveries. METHODS: From hospital discharge data in the 2018 National Inpatient Sample and State Inpatient Databases, we identified deliveries that were low-risk for cesarean delivery using the SMFM definition based on the International Classification of Diseases, Tenth Revision, Clinical Modification codes. We estimated national low-risk cesarean delivery rates overall and by patient characteristics, clinically relevant conditions not included in the SMFM definition, and hospital characteristics based on the nationally representative sample of hospital discharges in the National Inpatient Sample. Multivariate logistic regressions were estimated for the national sample to identify factors associated with low-risk cesarean delivery. We reported low-risk cesarean delivery rates for 27 states and the District of Columbia based on the annual state data that represented the universe of hospital discharges from participating states in the State Inpatient Databases. RESULTS: Of an estimated 3, 634, 724 deliveries in the 2018 National Inpatient Sample, 2, 484, 874 low-risk deliveries met inclusion criteria. The national low-risk cesarean delivery rate in 2018 was 14.6% (95% CI 14.4–14.8%). The rates varied widely by state (range 8.9–18.6%). Nationally, maternal age older than 40 years, non-Hispanic Black or Asian race, private insurance as primary payer, admission on weekday, obesity, diabetes, or hypertension, large metropolitan residence, and hospitals of the South census region were associated with low-risk cesarean delivery. CONCLUSION: Approximately one in seven low-risk deliveries was by cesarean in 2018 in the United States using the SMFM definition and the low-risk cesarean delivery rates varied widely by state. Abstract : Approximately one in seven low-risk deliveries was by cesarean in 2018 in the United States using the Society for Maternal-Fetal Medicine definition; the rates varied widely by state.